2015
DOI: 10.1109/tnb.2015.2388593
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized dSpliceType Framework to Detect Differential Splicing and Differential Expression Events Using RNA-Seq

Abstract: Transcriptomes are routinely compared in term of a list of differentially expressed genes followed by functional enrichment analysis. Due to the technology limitations of microarray, the molecular mechanisms of differential expression is poorly understood. Using RNA-seq data, we propose a generalized dSpliceType framework to systematically investigate the synergistic and antagonistic effects of differential splicing and differential expression. We applied the method to two public RNA-seq data sets and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…RNA-Seq libraries were prepared using the SMARTer® Stranded Total RNA Sample Prep Kit (634873 Clontech). Sequencing reads were aligned using STAR 50 , transcripts quantified using DESeq2 51 and differential splicing analysed by dSpliceType 52 . Random subsampling analysis via RSeQC 53 showed that the read coverage approached saturation of identified splice junctions, meaning that, statistically, all known and many of the novel junctions would have likely been identified at the coverage level achieved for all samples (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…RNA-Seq libraries were prepared using the SMARTer® Stranded Total RNA Sample Prep Kit (634873 Clontech). Sequencing reads were aligned using STAR 50 , transcripts quantified using DESeq2 51 and differential splicing analysed by dSpliceType 52 . Random subsampling analysis via RSeQC 53 showed that the read coverage approached saturation of identified splice junctions, meaning that, statistically, all known and many of the novel junctions would have likely been identified at the coverage level achieved for all samples (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless, there are several strategies that are commonly applied for differential splicing (DS) analyses. The more widelyused ones include a subgenic feature count-based method (e.g., DEXSeq [47], edgeR [48] and JunctionSeq [49]), or an event/junction-based method (e.g., dSpliceType [50], MAJIQ [51], and rMATS [52]). While the latter is able to more easily identify and classify types of alternative splicing changes, it suffers from less robust statistical power that is afforded by the former methodology [53].…”
Section: Ablation Of Tgsrs Tgclk and Tgprp4 Perturbs Alternative Splicingmentioning
confidence: 99%
“…The PCC between HACE1 and OPTN and corresponding P-values are 0.6059 and 0.0121, respectively. The OPTN and RAB25 have an opposite effect in the autophagy mechanism 52,86 . Based on the above mentioned information, we hypothesize the biological regulation mechanism as follows.…”
Section: Discussionmentioning
confidence: 98%